Effect of police training during the confinement period on some cardiopulmonary and hematological parameters in Khartoum, Sudan - Ahmed, Ahmed O.; Abdallah, Isam M.; Ali, Ibrahim A.; Musa, Omer A. (International Journal of Research in Medical Sciences, 2018)
Background: Pulmonary function tests (PFT) serve as a tool of health assessment and as a predictor of occupational fitness. Police officers must develop and maintain high levels of physical fitness for physical demanding tasks they perform. The training program starts with confinement of five to eight weeks according to the trainee. Previously it has been shown that the police students have better lung functions values compared to their civilian colleagues. In this study the effect of the confinement training on pulmonary function tests was investigated. Methods: Eighty one policemen trainee were randomly selected from a new batch in the faculty of police sciences and Law, the National Ribat University, Khartoum, Sudan at their starting confinement period. Subjects were medically fit with no history of Diabetes, Hypertension, Asthma or use of any long term medications. Pulmonary function tests (FVC, FEV1 and PEFR) were performed using a micro-plus spirometer. Blood pressure, pulse rate, and hemoglobin were measured. All these were repeated at the end of the confinement. Results: The age of participants ranged from 24 to 26 years. FVC, FEV1 and PEFR significantly increased after the confinement period. The blood pressure and the pulse significantly decreased. The weight of the participants decreased after the confinement but Hb significantly slightly increased. Conclusions: Regular police training during the confinement improved the pulmonary and cardiovascular reserve function.